NRF2 Alters Mitochondrial Gene Expression in Neonate Mice Exposed to Hyperoxia - Heather L. Vellers; Hye-Youn Cho; Wesley Gladwell; Kevin Gerrish; Janine H. Santos; Gaston Ofman; Laura Miller-DeGraff; T. Beth Mahler; Steven R. Kleeberger (MDPI AG, 2022)
Approximately 1 in 10 newborns are born preterm and require supplemental oxygen (O2) in an extrauterine environment following birth. Supplemental O2 can induce oxidative stress that can impair mitochondrial function, resulting in lung injury and increased risk in early life pulmonary diseases. The nuclear factor-erythroid 2 related factor 2 (NRF2) protects the cells from oxidative stress by regulating the expression of genes containing antioxidant response elements and many mitochondrial-associated genes. In this study, we compared Nrf2-deficient (Nrf2−/−) and wild-type (Nrf2+/+) mice to define the role of NRF2 in lung mitochondrial genomic features in late embryonic development in mice (embryonic days, E13.5 and E18.5) versus birth (postnatal day 0, PND0). We also determined whether NRF2 protects lung mitochondrial genome parameters in postnatal mice exposed to a 72 h hyperoxia environment. We found Nrf2−/− embryonic lungs were characterized by decreases in mtDNA copies from E13.5 to E18.5. Interestingly, Nrf2−/− heteroplasmy frequency was significantly higher than Nrf2+/+ at E18.5, though this effect reversed at PND0. In postnatal mice exposed to hyperoxia, we identified three- to four-fold increases in mitochondria-encoded mitochondrial genes, which regulate oxidative phosphorylation. Overall, our findings demonstrate a potentially critical role of NRF2 in mediating long-term effects of hyperoxia on mitochondrial function.